CFS IIUM students’ attitude towards assessments in selected courses in foundation programmes - Abdullah, Shamsuddin; Idris, Fathiyyatunnur (Centre for Foundation Studies International Islamic University Malaysia, 2023)
Education for Sustainable Development (ESD), the National Education Philosophy (NEP) or Falsafah Pendidikan Negara (FPK) and the IIUM Sejahtera Academic Framework (SAF) elaborated on importance of having high-quality educational assessments. Students’ attitude towards assessment practices serves as a perspective in checking this aspect in education. However, there has yet to be a study examining the students’ attitude towards courses in the Centre for Foundation Studies (CFS). Therefore, the purpose of this paper is to investigate the attitude toward assessments implemented in foundation programmes at CFS IIUM. The current study utilised the Students’ Feedback Survey (SFS) results focusing on items related to the purpose of this paper, which is the feedback on the amount of workload, the relevance of assessment tasks, variability of assessments, available supportive materials, and activities for the course. There are 3657 respondents with the method of convenience sampling and using the basic statistical function. The feedback on these five items were synthesised to determine students’ attitude toward the assessments of the courses. Results showed that students have positive attitudes towards the implementation of assessments for Human Sciences, Laws, and Islamic Revealed Knowledge courses at CFS where Laws’ students possess the highest satisfaction towards their course. In conclusion, this suggested that CFS is committed to providing high-quality assessment practices.